Cross section for forward J/psi production in p(p)over-bar collisions at root s=1.8 TeV - Acosta, D; Affolder, T; Akimoto, H; Albrow, MG; Ambrose, D; Amidei, D; Anikeev, K; Antos, J; Apollinari, G; Arisawa, T; Artikov, A; Asakawa, T; et al. (2002)
The inclusive cross section for J/ψ production times the branching ratio B(J/ψ→μ + μ -) has been measured in the forward pseudorapidity region: B×dσ[p̄+p→J/ψ(p r>10 GeV/c,2.1<|η|<2.6)+X]/dη = 192±9(stat) ±29(syst) pb. The results are based on 74.1±5.2 pb -1 of data collected by the CDF Collaboration at the Fermilab Tevatron Collider. The measurements extend earlier measurements of the D0 Collaboration to higher p TJ/ψ. In the kinematic range where the experiments partially overlap, these data are in good agreement with previous measurements.